Characterization of Central Nervous System Clinico-Genomic Outcomes in ALK-Positive Non-Small Cell Lung Cancer Patients with Brain Metastases Treated with Alectinib. (April 2023) - Miao, Emily; Eichholz, Jordan E.; Lebow, Emily S.; Flynn, Jessica; Zhang, Zhigang; Walch, Henry; Hubbeling, Harper; Beal, Kathryn; Moss, Nelson S.; Yu, Kenny K.; Meng, Alicia; Kelly, Daniel W.; et al.
Highlights: Extensive series of alectinib-treated lung cancer brain metastases with detailed lesion-level data and genomic correlates. No differences in clinical outcomes with alectinib only vs alectinib + local therapy. We saw a high frequency of CDKN2A/B copy number loss in our brain metastasis cohort. SMARCA4 co-alterations were associated with inferior overall survival. Abstract: Introduction: Highly effective brain-penetrant ALK- targeted tyrosine kinase inhibitors (TKIs) have been developed for the management of NSCLC patients with brain metastases (BM). Local therapy (LT) such as SRS or therapeutic craniotomy is increasingly being deferred for such patients. Herein we report detailed patient- and lesion-level intracranial outcomes and co-mutational genomic profiles from a cohort of NSCLC patients with BM treated with alectinib, with or without LT. Methods: We retrospectively reviewed ALK fusion-positive NSCLC patients with BMs who received alectinib at the diagnosis of BM from 1/2012 and 5/2021. Outcome variables included intracranial progression-free survival (iPFS), overall survival (OS), duration of TKI therapy, and CNS response rates. Genomic characteristics from tumor specimens were assessed with MSK-IMPACT, a next-generation sequencing (NGS)-based genomic profiling assay. Results: A total of 38 patients with 114 CNS lesions were included. Twelve of these patients also received contemporaneous LT (SRS, WBRT, or surgical resection). Maximal BM diameter in the TKI + LT group was greater (p < 0.003) but despite this difference, iPFS (TKI only, HR 1.21, 95 % CI 0.51–2.89; p = 0.66) and OS (TKI only, HR 5.99, 95 % CI 0.77–46.6; p = 0.052) were similar between groups and trended towards more favorable outcomes with the addition of LT. SMARCA4 co-alterations were associated with inferior OS (HR 8.76, 1.74–44.2; p = 0.009). Conclusions: Our study demonstrated that patients with ALK fusion-positive NSCLC treated with TKI + LT had larger BM and higher likelihood of pre-treatment neurologic symptoms. Despite these differences, iPFS was similar between groups. Results should be interpreted with caution as our study was limited by an underpowered sample size. SMARCA4 co-alterations were associated with inferior OS and these findings warrant further investigation.